High voltage insulation tester / Hayati Abdullah and Rusini Abdul Rashid - Abdullah, Hayati; Abdul Rashid, Rusini (1986)
The problem with using a multimeter to perform insulations tests is that it only tests at 1.5v DC. Very few components operate at this very low voltage so it really is no;t valid. It may easily give an open circuit reading when tested between the active leads and the frame. The peak voltage of the 240v AC mains is 340v which increases the chances of insulation breakdown enourmously. Add to that the strong possibility of spike voltages rising on top of the mains voltage and you can see why mains operated appliances have to have such good insulations. The same arguments apply when testing transformers, capacitors, high voltage semiconductors and other components, so these is a real need for a convenient self-contained insulation tester which can test at a voltage at least as high as that will be present in the circuit under normal operating conditions. The voltage most commonly used in tests of this kind are 500v and 1000v. A disadvantage of the majority of multimeters is their lack of resolution when measuring large resistances. Most multimeters simply read infinity (open circuit) when the resistance is above a few tens of megaohms.